Operation and Control of a Hybrid AC–DC Nanogrid for Future Community Houses - Chandrasena, Ruwan Pathiranage Sarath; Shahnia, Farhad; Ghosh, Arindam; Rajakaruna, Sumedha (Institute of Electrical and Electronics Engineers (IEEE), 2014)
A hybrid AC-DC nanogrid (NG) can be considered as the power supply system for future community houses. In this paper, the operation and control of a NG are presented. The NG consists of an AC bus and a DC bus, interconnected through a tie-converter. Each bus may have several loads and micro sources. The NG should have an adequate generation capacity to supply its loads in off-grid mode as well as the capability of exchangingpower with the utility grid. The tie-converter exchanges the power between two buses and regulates bus voltagein both buses in the case of off–grid operation. Several case studies are presented using PSCAD/EMTDC to verify the NG dynamics.